A Project of Attention: Still Life and the Everyday - Crocker, Mardi Laurel (Curtin University, 2018)
A Project of Attention: Still Life and the Everyday explores the affective dimension of contemporary western everyday life and the potential for the genre of still life painting to engage with and reflect the experience of it. Attending to the overlooked, the objects and bodily engagements that characterise the everyday, it assumes and advocates for a position of attunement and immersion in this field of research; a feeling for the affective texture and sensorial experience of the everyday.